Resonant Retiring? Experiences of Resonance in the Transition to Retirement - Bischoff, Luisa; Franke, Annette; Wanka, Anna (Frontiers in Sociology, 2021)
In the process of life course transitions, relations between the self and the world transform, which can according to Hartmut Rosa be framed as resonance. This article focuses on the retirement transition and thus on the exit from gainful employment as one of the central spheres of our world relationship in late modernity. It raises the following questions: How do experiences of resonance change in the course of the retirement transition? Does the loss of gainful employment lead to disruptions or even the absence of resonance in terms of alienation? And which role do dimensions of social inequality, such as gender, income, education or mental health status play for resonance transformations in the transition to retirement? In terms of a reflexive mixed-methods design, this article combines quantitative panel data from the German Ageing Survey (2008–17) with a qualitative longitudinal study from the project “Doing Retiring” (2017–21). Our results show that the transition from work to retirement entails a specific ‘resonance choreography’ that comprises a phase of disaffection (lack of resonance) at the end of one’s working life followed by a liminal phase in which people search for intensified experiences of resonance. We outline practices in which transitioning subjects seek out resonance, and the experiences they make within this process according to their social positions. We thereby find that the desire for resonance tends to be beyond intentional resonance management which manifests in products and services like coaching or wellness. In our conclusions, we discuss how resonance theory and retirement research/life course research can be fruitfully combined, but also highlight the methodological challenges the operationalization of resonance entails.